Tujuan Pemidanaan Dalam Kebijakan Pada Pembaharuan Hukum Pidana Indonesia - Muhammad Ramadhan; Dwi Oktafia Ariyanti (Jurnal Rechten : Riset Hukum dan Hak Asasi Manusia, 2023)
The problem in this research is regarding the policy formulation of the goals and guidelines for punishment in Indonesia as well as the objectives and guidelines for punishment in the context of reforming Indonesian criminal law in the future. The method in this study uses a normative juridical research type that is focused on examining the rules or norms in positive law. The policy on the formulation of the purpose of punishment needs to be studied to see what the goals and achievements are to be expected from a reform process in criminal law in this case related to the reorientation of the purpose of punishment. Knowing the aims and achievements of the purpose of sentencing will show the state's paradigm for the protection and guarantee of justice and the protection of human rights for its citizens as stated in its preamble. However, the purpose of punishment in the RKUHP needs to be reviewed to see how far the basis for the purpose of punishment and the forms of sanctions have been determined, because the determination of sanctions in the legislation is very important and strategic to achieve the objectives of the criminal law policy (penal policy).